Literasi Matematika Siswa SMP dalam Menyelesaikan Soal Setara AKM Konten Data dan Ketidakpastian Ditinjau dari Gaya Kognitif Reflektif-Impulsif - Vanesa Pramesuari Afra Kamila; Ismail Ismail (MATHEdunesa, 2026)
Mathematical literacy in data and uncertainty content among junior high school students remains relatively low, particularly in understanding, processing, and interpreting data in AKM-equivalent problems. While previous studies have mainly examined students’ achievement, limited research has described their mathematical literacy processes based on reflective and impulsive cognitive styles. This study aimed to describe students’ mathematical literacy processes in solving AKM-equivalent problems on data and uncertainty with socio-cultural contexts based on cognitive style. This study employed a qualitative descriptive approach involving two junior high school students representing reflective and impulsive cognitive styles, selected using a mathematics ability test and the Matching Familiar Figures Test (MFFT). Data were collected through mathematical literacy tests and interviews and analyzed descriptively. The results showed that reflective students identified information systematically, applied mathematical procedures carefully, and verified their calculations and conclusions before making decisions. In contrast, impulsive students solved problems more quickly but performed less evaluation and verification, leading to inaccuracies in several solutions. These differences were evident across the stages of formulating, employing, and interpreting. This study contributes by describing the characteristics of students’ mathematical literacy processes in AKM-equivalent problems from the perspective of reflective and impulsive cognitive styles.